We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
655
3
avatar

Find all zeros of the function f(x)=8x3−18x2−15x+25. Enter the zeros separated by commas.

 Jan 15, 2016

Best Answer 

 #2
avatar+101431 
+10

8x^3−18x^2−15x+25  = 0  

 

Since the sum of the coefficients =  0, then 1 is a root.......using synthetic divsion, we have

 

 

1  [  8     -18       -15        25  ]

                 8       -10       -25

       -------------------------------

       8     -10      -25        0

 

And the resultant polynomial set to 0 is

 

8x^2 -10x - 25 =  0       factor

 

[4x + 5] [2x - 5]  = 0

 

And each factor set to 0 produces the other two real roots :  -5/4    and  5/2

 

 

 

cool cool cool

 Jan 15, 2016
 #1
avatar
+10

Solve for x:
8 x^3-18 x^2-15 x+25 = 0

The left hand side factors into a product with three terms:
(x-1) (2 x-5) (4 x+5) = 0

Split into three equations:
x-1 = 0 or 2 x-5 = 0 or 4 x+5 = 0

Add 1 to both sides:
x = 1 or 2 x-5 = 0 or 4 x+5 = 0

Add 5 to both sides:
x = 1 or 2 x = 5 or 4 x+5 = 0

Divide both sides by 2:
x = 1 or x = 5/2 or 4 x+5 = 0

Subtract 5 from both sides:
x = 1 or x = 5/2 or 4 x = -5

Divide both sides by 4:
Answer: | x = 1,    or x = 5/2,    or x = -5/4

 Jan 15, 2016
 #2
avatar+101431 
+10
Best Answer

8x^3−18x^2−15x+25  = 0  

 

Since the sum of the coefficients =  0, then 1 is a root.......using synthetic divsion, we have

 

 

1  [  8     -18       -15        25  ]

                 8       -10       -25

       -------------------------------

       8     -10      -25        0

 

And the resultant polynomial set to 0 is

 

8x^2 -10x - 25 =  0       factor

 

[4x + 5] [2x - 5]  = 0

 

And each factor set to 0 produces the other two real roots :  -5/4    and  5/2

 

 

 

cool cool cool

CPhill Jan 15, 2016
 #3
avatar+101771 
+5

 

8x^3−18x^2−15x+25  = 0  

 

Since the sum of the coefficients =  0, then 1 is a root.......using synthetic divsion, we have

That is interesting Chris I have not ssen it expressed like that before

 

I would have used factor theory,

since  f(1) = 8-18-15+25=0 then 1 is a root which means that (x-1) is a factor.   etc

 Jan 15, 2016

10 Online Users